Self-assembly of plasmonic nanoparticles on optical fiber end face - Kularia, Muskan; Aftenieva, Olha; Sarkar, Swagato; Steiner, Anja M.; Gupta, Vaibhav; Fery, Andreas; Joseph, Joby; Schmidt, Markus A.; König, Tobias A.F. (Journal of Polymer Science, 2023)
Due to low losses, optical fibers are excellent optical waveguides, but manipulating the wavefront below the diffraction limit while keeping fabrication costs down is a significant challenge. Top-down lithographic methods can create arbitrary nanostructures on the fiber end face to manipulate the wavefront. Still, this method requires a flat fiber end face, which can only be made using elaborate preparation processes. We present a facile coating method in which we transfer a hexagonally packed monolayer of gold nanoparticles onto an untreated fiber end face. Using a poly(N-isopropylacrylamide) particle coating, we could transfer the free-floating monolayer from a water-air interface to the fiber end face. Our self-assembly method enables plasmonic gratings on rough surfaces and objects with large aspect ratios, which have been challenging for existing nanofabrication methods. Using electromagnetic simulation, we demonstrate the performance and utility of the concept as a refractive index sensor in which we consider different lattice constants. Our simulations cover possible analyses by calculating the structure under air, water, and polymer environments. Thus, we study the potential applications of low-cost fiber-based sensors with low optical losses.
CRIS-Team Scopus Importer:2023-05-26
Keywords: functional polymer; gold nanoparticle; nanostructured optical fibers; self-assembly; spectroscopy